2004
DOI: 10.1002/jsfa.1789
|View full text |Cite
|
Sign up to set email alerts
|

The effects of refined barley β‐glucan on the physico‐structural properties of low‐fat dairy products: curd yield, microstructure, texture and rheology

Abstract: The beneficial role of dietary fibre in human nutrition has lead to a growing demand for incorporation of novel fibres, particularly barley β-glucans, into foods. Barley β-glucans are regarded as dietary fibre ingredients that are partially soluble in water. The aim of the present work was to investigate the possibility of using barley β-glucan in milk systems in relation to the coagulation properties of milk containing β-glucan, and to the rheology, texture and microstructure of fresh curds. The rate of coagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 34 publications
8
47
1
1
Order By: Relevance
“…The microstructure of the control skim milk gel (Fig. 9a) compares favourably with previously reported results (Tudorica et al, 2004). The micrograph shows a dense, highly connected casein network with relatively small interstices.…”
Section: Effect Of Fibre Addition On Gel Microstructuresupporting
confidence: 86%
See 1 more Smart Citation
“…The microstructure of the control skim milk gel (Fig. 9a) compares favourably with previously reported results (Tudorica et al, 2004). The micrograph shows a dense, highly connected casein network with relatively small interstices.…”
Section: Effect Of Fibre Addition On Gel Microstructuresupporting
confidence: 86%
“…The incorporation of b-glucan into low fat cheese products has been investigated. Tudorica, Jones, Kuri, and Brennan (2004) explored the effect of fibre inclusion on curd formation. They showed that increasing levels of b-glucan resulted in decreased gel times and increased curd yields.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-and macro-structures of food products are imperative as methods for determining rheological and textural behaviour (Tudorica et al, 2004). Fig.…”
Section: Microstructurementioning
confidence: 99%
“…Recently, it was reported that the soluble polysaccharide, beta-glucan, from barley could act as a fat-replacer in low-fat cheese and yoghurt formulations to simulate the sensory properties of high fat products by improving texture and rheological properties (Brennan & Tudorica, 2008;Tudorica, Jones, Kuri, & Brennan, 2004). Moreover, exogenous addition of beta-glucan in the manufacture of non-fat yoghurt resulted in improved textural quality, improved water-holding capacity and acceptable sensory scores when beta-glucan levels were 0.5 g 100 g À1 (Sahan, Yasar, & Hayaloglu, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Tudorica et al [52] demonstrated that incorporation of β-glucans into low fat dairy products can make their mouthfeel, scoopability and sensory properties resemble those of full-fat products. Consequently, yogurt with oat-based β-glucan (OB) received higher scores for appearance, odor, color, taste, and overall acceptance than did yogurt containing barley-based β-glucan.…”
Section: International Journal Of Chemicalmentioning
confidence: 99%